Extending the Minority Stress Model to Incorporate HIV-Positive Gay and Bisexual Men's Experiences: a Longitudinal Examination of Mental Health and Sexual Risk Behavior. Issue 2 (8th August 2016) - Rendina, H. Jonathon; Gamarel, Kristi E.; Pachankis, John E.; Ventuneac, Ana; Grov, Christian; Parsons, Jeffrey T.
Abstract: Background: Minority stress theory represents the most plausible conceptual framework for explaining health disparities for gay and bisexual men (GBM). However, little focus has been given to including the unique stressors experienced by HIV-positive GBM. Purpose: We explored the role of HIV-related stress within a minority stress model of mental health and condomless anal sex. Methods: Longitudinal data were collected on a diverse convenience sample of 138 highly sexually active, HIV-positive GBM in NYC regarding sexual minority (internalized homonegativity and gay-related rejection sensitivity) and HIV-related stressors (internalized HIV stigma and HIV-related rejection sensitivity), emotion dysregulation, mental health (symptoms of depression, anxiety, sexual compulsivity, and hypersexuality), and sexual behavior (condomless anal sex with all male partners and with serodiscordant male partners). Results: Across both sexual minority and HIV-related stressors, internalized stigma was significantly associated with mental health and sexual behavior outcomes while rejection sensitivity was not. Moreover, path analyses revealed that emotion dysregulation mediated the influence of both forms of internalized stigma on symptoms of depression/anxiety and sexual compulsivity/hypersexuality as well as serodiscordant condomless anal sex. Conclusions: We identified two targets of behavioral interventions that may lead to improvements in mental health and reductions in sexual transmission risk behaviors—maladaptive cognitions underlying negative self-schemas and difficulties with emotion regulation. Techniques for cognitive restructuring and emotion regulation may be particularly useful in the development of interventions that are sensitive to the needs of this population while also highlighting the important role that structural interventions can have in preventing these disparities for future generations.